Electrochemical Redox Processes Involved in Carbon-Coated KVPO4F for High Voltage K-Ion Batteries Revealed by XPS Analysis. Issue 13 (1st October 2020) - Caracciolo, Laure; Madec, Lénaïc; Petit, Emmanuel; Gabaudan, Vincent; Carlier, Dany; Croguennec, Laurence; Martinez, Hervé
Abstract : K-ion batteries need efficient positive electrode materials with open structural frameworks to accommodate the large ionic radius of K + . In that direction, polyanionic compounds are of great interest. Among them, KVPO4 F is the most studied one. Its electrochemical redox processes still remain unclear, especially at high voltage. To tackle this issue, X-ray photoelectron spectroscopy was used to reveal the electrochemical redox processes of Kx VPO4 F. First, a carbon coating was performed and allowed increasing the overall electrochemical performance while mitigating electrolyte degradation at high voltage. Then, XPS analysis showed a high reversibility of the redox processes although the K + extraction (and insertion) from x = 0.5 to 0 was hindered, possibly by structural constraints while electrolyte degradation occurred mostly above 4.5 V.